2002
DOI: 10.1103/physrevc.65.061604
|View full text |Cite
|
Sign up to set email alerts
|

Origins of intermediate velocity particle production in heavy ion reactions

Abstract: Investigation of intermediate-velocity particle production is performed on entrance channel mass asymmetric collisions of 58 Ni+C and 58 Ni+Au at 34.5 MeV/nucleon. Distinctions between prompt pre-equilibrium ejections, multiple neck ruptures and an alternative phenomenon of delayed aligned asymmetric breakup is achieved using source reconstructed correlation observables and time-based cluster recognition in molecular dynamics simulations. PACS number(s): 25. 25.70.Lm, 25.70.Mn, 25.70.Pq During the last dec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Experimental and theoretical studies have indicated that the midrapidity particles are produced from a combination of complex mechanisms. Gingras et al used a molecular dynamics simulations to show that the formation of the midrapidity particles could be attributed to both a prompt emission, due to nucleon-nucleon collisions, and a later emission from the tails of the QP and QT [19]. Similarly, three-body Coulomb trajectory calculations showed that the production of midrapidity IMFs could be connected to both a fast emission from the neck region and a later emission from the surface of the QP or QT [20].…”
Section: Introductionmentioning
confidence: 99%
“…Experimental and theoretical studies have indicated that the midrapidity particles are produced from a combination of complex mechanisms. Gingras et al used a molecular dynamics simulations to show that the formation of the midrapidity particles could be attributed to both a prompt emission, due to nucleon-nucleon collisions, and a later emission from the tails of the QP and QT [19]. Similarly, three-body Coulomb trajectory calculations showed that the production of midrapidity IMFs could be connected to both a fast emission from the neck region and a later emission from the surface of the QP or QT [20].…”
Section: Introductionmentioning
confidence: 99%
“…The process of deeply inelastic diffusion becomes the dominant phenomenon [4][5][6][7][8]. It is accompanied by an important emission of light particles, thermally unbalanced [8][9][10]. But we also observe an important production of Intermediate Mass Fragments (IMFs) at the interface of the two colliding nuclei.…”
Section: Introductionmentioning
confidence: 78%
“…The collisions present mostly a strong binary character preserving a very strong memory of the entrance channel [3]. The process of deeply inelastic diffusion becomes the dominant phenomenon [4][5][6][7][8]. It is accompanied by an important emission of light particles, thermally unbalanced [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Instead of simply calculating integrals and subtracting distributions, probability tables are constructed [21], based on the forward QP emission distributions for each Z < 5 isotope. These tables allow us to allocate particles to the QP and the MR emission sources while keeping available complete information about these particles.…”
mentioning
confidence: 99%